2011
DOI: 10.3892/mmr.2011.578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the expression of DNA methyltransferase proteins in gastric cancer

Abstract: Abstract. DNA methyltransferase (DNMT) 1, DNMT3A and DNMT3B, which affect promoter CpG methylation status, play a significant role in cancer development. Little is known regarding the clinical significance of DNMT expression in gastric cancers. Expression of DNMT1, DNMT3A and DNMT3B in paraffin sections from 54 gastric cancer patients were examined using immunohistochemistry, and their associations with the corresponding clinicopathological parameters were analyzed using the Chi-square test. Overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Some studies demonstrated that there is a coordinate action of the DNMTs. 32,33 In accordance, a significant correlation between the expression of these enzymes was observed in the present study, suggesting that there is a cooperative action of the DNMTs expression in pediatric MDS pathogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies demonstrated that there is a coordinate action of the DNMTs. 32,33 In accordance, a significant correlation between the expression of these enzymes was observed in the present study, suggesting that there is a cooperative action of the DNMTs expression in pediatric MDS pathogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…DNMTs were a predominant cause of DNA methylation and the differential expression of DNMTs has been identified in numerous types of cancer (4143), including EOC, which we previously reported (32). It was hypothesized in the present study that the over-expression of DNMT proteins may contribute to BRCA1 methylation; therefore, the association between BRCA1 methylation and DNMT protein expression was analyzed.…”
Section: Discussionmentioning
confidence: 56%
“…In eukaryotic cells, there are three enzymatically active DNA methyltransferases (DNMTs), DNMT1, DNMT3A and DNMT3B. The expression of DNMT3A in GC is significantly higher than that of DNMT3B [ 32 , 33 ]. Moreover, only increased DNMT3A expression is significantly associated with a shorter disease-free survival period in GC [ 34 ], which indicates DNMT3A plays more important roles in gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%